2022
DOI: 10.1590/0001-3765202220201206
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral isolation and demographic stability are reflected in the genetic diversity of the populations of the Helmeted Manakin: a bird endemic to the gallery forests

Abstract: The Cerrado encompasses a complex network of hydrographic basins, which is responsible for the formation and maintenance of the riparian and gallery forests.Alterations in the vegetation resulting from the paleoclimatic changes that occurred during the Pleistocene influenced the current distribution of these humid forests. To understand of the evolutionary dynamics of this landscape on the population structure of the associated organisms, we studied the population genetics of the Antilophia galeata (Pipridae),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…This pattern may be caused by human intervention in the introduction and breeding of endemic endangered breeds and the demarcation of nature reserves for endemic endangered breeds to protect their natural reproduction from environmental threats. The increased occurrence of extreme weather events caused by global warming and climate change might affect the population fluctuation patterns of endemic endangered breeds [54]. This study found that the neutral-ity test Fu's Fs of WZ and YJ geese were close to zero, and Tajima's D was positive.…”
Section: Discussionmentioning
confidence: 70%
“…This pattern may be caused by human intervention in the introduction and breeding of endemic endangered breeds and the demarcation of nature reserves for endemic endangered breeds to protect their natural reproduction from environmental threats. The increased occurrence of extreme weather events caused by global warming and climate change might affect the population fluctuation patterns of endemic endangered breeds [54]. This study found that the neutral-ity test Fu's Fs of WZ and YJ geese were close to zero, and Tajima's D was positive.…”
Section: Discussionmentioning
confidence: 70%
“…The outer layer of the ring of cells shows the total number of addressed hypotheses (not studies; studies may address ≥1 or 0 hypotheses) showing full support, mixed support, or no support for the given category, while the inner layer pertains to the corresponding ribbon. Am, Amphibian; An, Animal González-Ittig et al, 2022;birds: Corbett et al, 2020;Lima-Rezende et al, 2019;Luna et al, 2017;Rocha et al, 2020;Souza et al, 2022;invertebrates: Andrade-Souza et al, 2017;Barrios-Leal et al, 2019;Fernández Campón et al, 2021;Franco & Manfrin, 2013;Françoso et al, 2016;Moraes et al, 2009). The Caatinga's formation occurred during the Neogene and Pleistocene, with an SDTF flora assembling in the region as regional aridification and the exhumation of Paleo-Mesozoic sediments promoted environmental heterogeneity (Fernandes et al, 2022).…”
Section: Pleistocene Climate Fluctuationsmentioning
confidence: 99%
“…For Cerrado reptiles, the effects of Pleistocene climate change may therefore be limited to demographic changes. Other animal taxa studied in this context have generally shown demographic changes and/or changes in population structure in response to Pleistocene climatic fluctuations (mammals: Di‐Nizo et al., 2022; González‐Ittig et al., 2022; birds: Corbett et al., 2020; Lima‐Rezende et al., 2019; Luna et al., 2017; Rocha et al., 2020; Souza et al., 2022; invertebrates: Andrade‐Souza et al., 2017; Barrios‐Leal et al., 2019; Fernández Campón et al., 2021; Franco & Manfrin, 2013; Françoso et al., 2016; Moraes et al., 2009).…”
Section: Climatic Drivers Of Diversification In the Dry Diagonalmentioning
confidence: 99%